2004
DOI: 10.1677/joe.0.1820043
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies and production rate of equine (e) FSH in ovariectomized pony mares. Application to the determination of a dosage regimen for eFSH in a superovulation treatment

Abstract: The appropriate dosage regimen for equine FSH (eFSH) (dose, dosing interval) administration in a superovulation treatment in pony mares was determined by a kinetic approach using production rates and kinetic parameters of elimination of the hormone. Two dosage regimens were then tested in superovulation protocols. The eFSH production rates were determined by sampling four ovariectomized pony mares every 10 min for 8 h during the breeding season. Kinetic parameters were determined by administering four dose lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This variability may, in part, relate to one of the intrinsic limitations of a brain extract such as eFSH; the exact gonadotrophin composition, in particular the ratio of FSH to LH, is likely to differ between batches and this may contribute to variability in response. Too low a dose of FSH would result in a poor superovulatory response, while too high a dose (or too high an LH:FSH ratio) may predispose to luteinisation of follicles without ovulation (Briant et al 2004).…”
Section: Multiple Ovulationmentioning
confidence: 99%
“…This variability may, in part, relate to one of the intrinsic limitations of a brain extract such as eFSH; the exact gonadotrophin composition, in particular the ratio of FSH to LH, is likely to differ between batches and this may contribute to variability in response. Too low a dose of FSH would result in a poor superovulatory response, while too high a dose (or too high an LH:FSH ratio) may predispose to luteinisation of follicles without ovulation (Briant et al 2004).…”
Section: Multiple Ovulationmentioning
confidence: 99%
“…If the dose is too high, the ovaries become overstimulated and many of the follicles do not ovulate but become luteinized or develop an anovulatory follicle. Briant and coworkers [29] reported that if the dose of eFSH was too high, progesterone concentrations higher than 1 ng/mL were detected in treated mares before ovulation. This premature progesterone concentration was attributable to elevated LH, which resulted in premature ovulation or luteinization of follicles.…”
Section: Potential Problems After Superovulationmentioning
confidence: 99%
“…Superovulation in horses is much less successful than in other domestic species. In addition to superovulation rate, the number of embryos are typically negligible (1). Hence, there is a great demand to develop products that induce multiple ovulations in mares due to changes in the governance of the horse reproduction industry (2).…”
Section: Introductionmentioning
confidence: 99%